Outcomes of Patients With Advanced NSCLC From the Intergroupe Francophone de Cancérologie Thoracique Biomarkers France Study by KRAS Mutation Subtypes - Anne-Marie Ruppert, MD, PhD; Michèle Beau-Faller, MD, PhD; Didier Debieuvre, MD; L’Houcine Ouafik, MD, PhD; Virginie Westeel, MD PhD; Isabelle Rouquette, MD; Julien Mazières, MD, PhD; Pierre-Paul Bringuier, MD; Isabelle Monnet, MD; Fabienne Escande, MD; Charles Ricordel, MD; Jean-Philippe Merlio, MD, PDh; et al. (JTO Clinical and Research Reports, 2020)
Introduction: KRAS mutations are detected in 20% to 30% of NSCLC. However, KRAS mutation subtypes may differently influence the outcome of patients with advanced NSCLC. Methods: In the Biomarkers France study, 4894 KRAS mutations (26.2%) were detected in 4634 patients from the 17,664 enrolled patients with NSCLC. Survival and treatment data on noncurative stage III to IV NSCLC were available for 901 patients. First- and second-line treatment effects on progression-free survival and overall survival were analyzed according to the KRAS mutations subtype. Results: Over 95% of patients with KRAS mutation were smokers or former smokers who were white (99.5%), presenting with adenocarcinoma (82.5%). The most common KRAS mutation subtype was G12C (374 patients; 41.5%), followed by G12V (168; 18.6%), G12D (131; 14.5%), G12A (62; 6.9%), G13C (45; 5.0%), G13D (31; 3.4%), and others (10; 1%). Approximately 21% of patients had transition mutation and 68.2% had a transversion mutation. G12D and transition mutations were predominant in never-smokers. The median overall survival for patients with KRAS-mutated NSCLC was 8.1 months (95% confidence interval [CI]: 7.5–9.5), without any differences according to the different KRAS subtypes mutations. The median progression-free survival was 4.6 months (95% CI: 4.2–5.1) for first-line treatment and 4.8 months (95% CI: 4.3–6.8) for second-line treatment, without any differences according to the different KRAS subtypes mutations. Conclusions: KRAS mutation subtypes influenced neither treatment responses nor outcomes. The KRAS G12C mutation was detected in 41.5% of patients, who are now eligible for potent and specific G12C inhibitors.